Tinjauan Kriminologis terhadap Tindak Pidana Penelantaran Anak Oleh Orang Tua di Kepolisian Resor Kota Jambi - Fauzia, Nur; Hisbah, Hisbah; Lestari, Dini Ayu (Universitas Batanghari Jambi, 2024)
Child neglect by parents is very often found in society, including in Jambi. Based on data from the Women and Children Protection Unit (PPA) of the Jambi City Police, in the 2020-2022 period there were at least 8 (eight) cases of child neglect. For this reason, the author will examine this problem with the help of criminological science to obtain conclusions regarding the factors that cause the crime of child neglect, the obstacles faced by the Jambi City Resort Police PPA, and also efforts to overcome them. The research method used is empirical juridical with interview techniques. The results of related research suggest that the factors causing the crime of child neglect by parents in Jambi City are economic factors, internal family factors and also environmental factors. The obstacles faced by the Jambi City Police PPA Unit in handling the crime of child neglect by parents are difficulties in collecting evidence and witnesses and related parties not being cooperative. Efforts to overcome this criminal act are pre-emptive, preventive and finally repressive.